2010
DOI: 10.1007/s10755-010-9157-5
|View full text |Cite
|
Sign up to set email alerts
|

21st Century Competencies for Doctoral Leadership Faculty

Abstract: Graduate and post-graduate programs were initially developed by universities to increase discipline-specific mastery. Faculty members impact both the content and quality of such programs as they are responsible for making it relevant in the current climate while also addressing the changes envisaged for society tomorrow. Although studies exist regarding faculty competencies in various disciplines and for preparing future faculty members, there is a paucity of research specific to competencies necessary for fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 26 publications
0
42
0
1
Order By: Relevance
“…Second, that there is a list of competencies that supervisors can gain, strengthen, and be measured by. Hyatt and Williams (2011, p. 58-60) Note: these factors are adopted directly from Hyatt & Williams (2011) with the exception that the language has been adjusted in several instances to make each part more consistent with the whole.…”
Section: Supervisory Issuesmentioning
confidence: 99%
“…Second, that there is a list of competencies that supervisors can gain, strengthen, and be measured by. Hyatt and Williams (2011, p. 58-60) Note: these factors are adopted directly from Hyatt & Williams (2011) with the exception that the language has been adjusted in several instances to make each part more consistent with the whole.…”
Section: Supervisory Issuesmentioning
confidence: 99%
“…Management of research skills referred to understanding of the scientific method and research process (Harrison, Hernandez, Cianelli, Rivera, & Urrutia, ; Stubb, Pyhältö, & Lonka, ). Knowledge of research methodology included managing databases and searches, knowledge of research designs and an ability to formulate research questions, to know and elaborate research frameworks and to be familiar with statistical programmes and analyses (Baltes, Hoffman‐Kipp, Lynn, & Weltzer‐Ward, ; Harrison et al, ; Lim, Daniels, & Watkins, ; Sunderland, ) as well as scholarly and researcher skills including writing research proposals (Hyatt & Williams, ; Lou & Chen, ; Welton, Mansfield, Lee, & Young, ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified that certain attributes and competencies, including debriefing, providing constructive feedback, mentoring and support in practical elements of a PhD, are essential skills that supervisors require 26 . Some of the students in this study reported issues with receiving feedback that could be linked to lack of teaching time.…”
Section: Discussionmentioning
confidence: 99%